THE CORRELATION BETWEEN KNOWLEDGE WITH ATTITUDES OF ADOLESCENTS IN CONSUMING IRON TABLETS AT SMP NEGERI 2 KABANJAHE, KABANJAHE DISTRICT, KARO REGENCY IN 2023 - Srilina Br Pinem; Ninsah Mandala Putri Sembiring; Marlina Simbolon; Ernamari Ernamari; Srievadiana Br. Sembiring; Pita Nova Br. Ginting (Department of Midwifery, Faculty of Nursing and Midwifery, Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2023)
Lack of iron in adolescents without balanced adequate iron intake will continue during pregnancy when pregnancy will cause fetal growth is not optimal, low birth weight, the risk of bleeding during labor and increase the risk of maternal and infant death. Therefore most Obstetrics and Nutrition experts recommend iron supplements from preconception (adolescence). This was an analytical research with a Cross Sectional design, where researchers take samples from a population using a questionnaire as a data collection tool to determine the relationship between knowledge and attitudes of adolescents in consuming iron tablets at SMP Negeri 2 Kabanjahe, Karo Regency, North Sumatra Province in 2023. Results of a study conducted by the author entitled